Intraoral approach for zygomatic sialoadenectomy in dogs: An anatomical study and three clinical cases. Issue 2 (11th November 2022) - Viitanen, Joni; de Rooster, Hilde; Kitshoff, Adriaan; Arzi, Boaz; Devriendt, Nausikaa
Abstract: Objective: To describe an intraoral approach (IOA) for zygomatic sialadenectomy in dogs and to compare this surgical approach to a modified lateral orbitotomy approach (LOA). Study design: Cadaveric study and short case series. Sample population: Ten canine cadavers and three dogs with clinical disease. Methods: Bilateral zygomatic sialoadenectomies were performed in six mesocephalic, two brachycephalic and two dolichocephalic cadavers, randomly assigned to IOA on one side and LOA on the contralateral side. Duration of surgery, ease of surgical stage scores (rated on 5‐point Likert scale) and completeness of gland removal were recorded. Additionally, IOA was performed in three dogs with zygomatic salivary gland (ZSG) disease. Results: Removal of the ZSG was complete in 8/10 and 10/10 dogs using the IOA and LOA, respectively. Surgery was faster with IOA (42.0 min; 33.5–49.6 min) than LOA (65.7 min; 54.9–76.4 min, p = .005). Ease of removal did not differ between approaches ( p = .091). Diseased ZSGs were successfully removed in three dogs without intra‐ or short‐term postoperative complications. Conclusions: The intraoral approach described here was technically equally challenging but faster than the LOA. Its clinical use led to an uneventful surgery with excellent short‐term outcome in three dogs. Clinical relevance: The IOA provides an alternative approach for zygomatic sialoadenectomy in dogs with ZSG disease.